Influence of soil use and occupation on the surface flow slide in the São Benedito river hydrographic microbasin (International Journal of Geoscience, Engineering and Technology, 2022)
Knowing about the surface runoff is an important information in the context of planning and integrated management of hydrographic basins. The objective of this research is to analyze the influence of land use and occupation on the surface runoff in the Ribeirão São Benedito watershed, located in Teófilo Otoni/MG, in the years 2013 and 2021. To estimate the surface runoff in the watershed, the CN method (USDA, 1954) of the National Service for the Conservation of Natural Resources (NRCS) of the United States Department of Agriculture (USDA) was used. It was found, between the years 2013 and 2021, that there was an increase of 2% in the surface runoff. This was mainly due to the increase in exposed soil in the watershed.